Target Zero Injury: A Strategy for Mitigating Hospital-Acquired Pressure Ulcers - Chandni; Teli, Sunita; Jaison, Shainy; Roy, Jaya; John, Minimole; Sebastian, Susan (International Journal of Research in Medical Surgical Nursing, 2024)
Despite advancements in technology, education, and awareness, pressure ulcers continue to burden patients and healthcare facilities. The number of admissions with an increasing dependency and understanding of patients, particularly in the ICU, can be a contributory factor for pressure injury. Furthermore, there has been a concerning trend of hospital-acquired pressure damage, with up to 2-3 patients per month developing such injuries. Addressing Hospital Acquired Pressure Injury (HAPI) is crucial as it is preventable harm to patients. In a selected institute, hospital-acquired pressure injuries have shown an alert rise, from 0.076 cases per 1000 patient days in 2021 to a spike of 0.170 per 1000 patient days in 2023. This emphasizes the urgent need for effective preventive measures and interventions to mitigate the occurrence of these injuries. The study was conducted to eradicate all instances of hospital-acquired injuries within the designated hospital and decrease the number of pressure injury cases by 50% compared to the previous year by December 2023. The patient is susceptible to pressure injury due to various factors, including immobility, skin breakdown, incontinence, poor perfusion, and medical devices. It is estimated that nearly 95% of pressure injuries can be avoided. If patients at risk of developing pressure injuries are not identified during their hospitalization, timely interventions may not be possible. The outcome of staff gaining enhanced knowledge and confidence through discussions on pre-equipped beds featuring high specification pressure redistributing mattresses, education, and a pressure management algorithm has shown significant clinical advantages by preventing HAPI. Hence, hospital-acquired pressure injuries are preventable. If all nurses were equipped with the right tools, the proper care bundle, and early recognition of high-risk patients with appropriate health education programs, it would help hospitals achieve optimal patient care.